2019
DOI: 10.5860/crl.80.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration, Consultation, or Transaction: Modes of Team Research in Humanities Scholarship and Strategies for Library Engagement

Abstract: With the rise of digital scholarship, humanists are participating in increasingly complex research teams and partnerships, and academic libraries are developing innovative service models to meet their needs. This paper explores modes of coworking in humanities research by synthesizing responses from two qualitative studies of research practices in the humanities and proposes a taxonomy of multiperson research that includes collaborative, consultative, and transactional research partnerships among scholars, gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Regarding other aspects of data management, our results differ from previous studies (Akers and Doty, 2013; Thoegersen, 2018) as far as the willingness to share research data with colleagues is concerned: we found collaboration to be extremely important for our interviewees, both in the form of informal sharing and of teamwork. A possible explanation might be found in the influence of DH projects, which are intrinsically more collaborative as they “require human and material resources spanning disciplinary and institutional boundaries” (Senseney et al ., 2019). However, as explained in the methods section, we were unable to analyse DH as a separate disciplinary area.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other aspects of data management, our results differ from previous studies (Akers and Doty, 2013; Thoegersen, 2018) as far as the willingness to share research data with colleagues is concerned: we found collaboration to be extremely important for our interviewees, both in the form of informal sharing and of teamwork. A possible explanation might be found in the influence of DH projects, which are intrinsically more collaborative as they “require human and material resources spanning disciplinary and institutional boundaries” (Senseney et al ., 2019). However, as explained in the methods section, we were unable to analyse DH as a separate disciplinary area.…”
Section: Discussionmentioning
confidence: 99%
“…A significant body of library literature discusses scholarly communication outreach and programing for university patrons, and many studies find that collaboration across the institution is key (Cantrell & Johnson, 2018;Eddy & Solomon, 2017;Fong, 2019;Schulte et al, 2018;Senseney et al, 2019). Even solo librarians at small academic institutions can benefit from partnerships to scaffold this type of instruction (Rios, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fong provides a framework and recommendations for building collaborative workshops for graduate students in their article about grant-funded scholarly communication boot camps (2019). Researchers are increasingly pursuing digital and interdisciplinary scholarship, so looking at digital humanists to study and collaborate with for scholarly communication education can provide inspiration for partnerships and programing (Coble et al, 2014;Senseney et al, 2019). Working with students on open access and university policies can be a way to directly influence a student's research identity (Cantrell & Johnson, 2018), and creating learning communities for faculty to engage in conversations about research is an effective way to form lasting connections for researchers to scholarly communication topics (Bazeley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%